The Effect of The Project Based Learning Model on The Implementation of Deep Learning in Improving Mathematics Learning Outcomes - Wilda Anisa Ukhro Sinaga; Nurlina Ariani Harahap; Laili Habibah Pasaribu (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This research is focused on enhancing the mathematics achievement of students in eleventh grade in the area of Statistics by utilizing Project Based Learning to facilitate deep learning. The approach adopted is a quasi-experimental design with pre-tests and post-tests involving two groups of 72 students (with XI-1 as the experimental group and XI-4 as the control group) employing essay assessments and observational methods at SMA Negeri 1 Aek Natas. Findings revealed that the average post-test score for the experimental group improved by 19.17, surpassing the control group's score of 17.08. The independent sample t-test yielded a significant value of 0.007 (<0.005), indicating a notable difference between the two groups. Furthermore, the N-gain for the experimental group was 41.19% (medium category), significantly greater than the 5.8% (low category) recorded for the control group. In summary, the utilization of Project Based Learning (PJBL) in the experimental class effectively contributes to the enhancement of mathematics learning outcomes and promotes student participation in mathematics education within secondary schools.